Estudo do ciclo do nitrogênio em lagoas de estabilização tratando esgotos domésticos no Nordeste do Basil - Silva, Fernando José Araújo da (1994)
The behaviour of nitrogen compounds was investigated in two pilot-scale pond systems (Systems XVI and XVII) treating domestic sewage from Campina Grande, Paraíba, northeast Brazil (7° 13' 11'' S, 35° 52' 31'' W, 550 above mean sea level). System XVI comprised two parallel anaerobic ponds (A9 and A10), followed by five parallel secondary facultative ponds (F21 to F25), one primary maturation pond (M15), five parallel secondary maturation ponds (M16 to M20) and four parallel tertiary maturation ponds (M21 to M24). These ponds have different depths and hydraulic retention times were arranged to form series with different configurations. System XVII was a long series of 1.5 m deep pond being the anaerobic pond (A11) fed with raw sewage followed by a secondary facultative pong (F26) and eight maturation ponds (M25 to M32). The systems of the experimental complex were investigated between June and December 1992. Monitoring was based on column samples (System XVI) and on both grab and column samples (System XVII). Pond samples (column and effluent0 and raw sewage daily composite samples were analysed for the following parameters: Total Kjeldahl Nitrogen, Ammonia, Organic Nitrogen, Nitrate, Nitrite, Temperature, pH, Dissolved Oxygen, Biochemical Oxygen Demand, Suspended Solids and Chlorophyll "a". Results showed that nitrogen occurred mainly by ammonia stripping in maturation ponds due high pH values in these ponds. System XVI attained an efficiency of 90% in ammonia removal, where System XVII reached efficiencies of 77 and 71% for effluent and column samples, respectively. Organic nitrogen was removed in the anaerobic ponds (round 50%). The organic nitrogen concentration in the final effluent of System XVI was about 10 mg N/l. By contrast, the concentration in System XVII was found to be about half (5 mg N/l) the concentration in the long series. Both systems showed low concentrations of nitrite and nitrate. Being higher in System XVII than in System XVI.